Nutrient harvest and soil fertility as influenced by legume-wheat (Triticum aestivum) sequences - PRASAD, N K; KUMAR, SANJAY (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1993-95 to assess the contribution of preceding legume crop on succeedingwheat (Triticum aesfivum L. emend. Fiori & Paol) for crop production, nutrient harvest and balance of the same in soilunder recommended doses of nutrients of khari crops and variable levels of nitrogen to succeeding wheat. Blackgram(phaseolus mango L.) as a preceding crop to wheat resulted in the maximum wheat production while stylo (Stylosantheshamata L.) - wheat sequence accounted for higher wheat equivalent yield. Application of 75 kg N/ha to wheat grownafter legume was as good as to wheat yield received at 100 kg N/ha after legume. Soybean (Glycine max (L.) Merr.)wheatsequence has removed the maximum quantity of N while wlieat grown after blackgram harvested the maximumquantity of N. Soybean - wheat sequence further removed the highest quantity of P but stylo - wheat sequence recordedthe maximum recovery of K. Though all the legume - wheat sequences have recorded better build up in soil N,however, wheat grown after blackgram at 100 kg N/ha recorded the maximum build up in available soil N while wheatgrown in absence of external N has left over maximum available P in soil. General increase in available K was noticedunder all the sequences to their initial status.